Potential for Digital-Based Productive Waqf Development (Case Study of Datuk Sulaiman ModernIslamic Boarding School and Muhammadiyah Boarding School) in Palopo City, South of Celebes - Muhammad Fachrurrazy; Dirah Nurmila Siliwadi; Nur Herlina (Institut Agama Islam Negeri (IAIN) Curup, 2022)
Purpose: This study was to identify and analyze digital-based productive waqf management procedures according to existing regulations for the development of productive waqf in Islamic boarding schools in Palopo City.Design/Method/Approach: This research uses empirical and qualitative descriptive research as the method; the approach of this research is a case study. The subjects/informants of this research are elements of leadership and management at Datuk Sulaiman Islamic Boarding School and Muhammadyah Boarding School by means of observation, interviews, and documentation as the core analysis of research data.Findings: The result of this research is that Datuk Sulaiman Islamic Boarding School (PMDS) and Muhammadiyah Islamic Boarding School have great potential to realize an economic movement and independence with the concept of productive waqf in Islamic boarding schools. Supporting the management and optimization of existing (traditional) waqf by using productive waqf instruments and utilizing digital technology facilities that have developed the pesantren economy.Organally/Value: This research is expected to provide the development of waqf efforts from the portrait of the fact that most of the management of waqf empowerment in Indonesia has not been touched productively and its management is through a digital base.